Hand hygiene: An educational intervention targeting grass root level. Issue 3 (May 2019) - Chauhan, Kalpana; Pandey, Anita; Thakuria, Bhaskar
Abstract: Background: Hands are the most common vehicle for the transmission of pathogens within the healthcare environment. Hand hygiene is the leading measure for reducing healthcare-associated infections (HCAIs) and preventing the spread of antimicrobial resistance. Objective: An interventional study was carried out to evaluate the knowledge, attitude and practices of hand hygiene among third semester medical students. Materials and methods: A total of 152 medical students were evaluated using a pretest self-structured questionnaire to assess the knowledge, attitude and practices regarding hand hygiene. The students were trained by faculty of microbiology vigorously with the help of a lecture and demonstration on hand hygiene followed by hands-on training. The same group of students were then distributed the post-training questionnaire. The pre-training and post training data was analyzed and compared. Result: There was a significant improvement in knowledge, attitude and practice towards hand hygiene among students after intervention, as seen on comparison of results of post-test questionnaire from its pre-test counter-part because the doubts in the mind of the students got cleared in the education sessions. Conclusion: Targeting medical students and teaching them the good standard practices was fruitful as they were young, easy to mold and enthusiastic and above all they are the future doctors. Such educational intervention regarding hand hygiene will be carried out for each batch of medical students in future.